Pengaruh Responsiveness dan Promosi Penjualan terhadap Keputusan Pembelian Mobil Mitsubishi pada PT Dipo Internasional Pahala Otomotif Cabang Ringroad Medan - Peby Monica; T. Teviana (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
This study aims to analyze the effect of responsiveness and sales promotion on the purchase decision of Mitsubishi cars at PT Dipo Internasional Pahala Otomotif, Ringroad Medan Branch. The research is motivated by the phenomenon of a 13.58% decline in sales and a 43.33% increase in customer complaints during the 2024–2025 period. This study employed a quantitative approach with a survey method. The population consisted of 439 consumers, and a sample of 82 respondents was selected using purposive sampling. Data were collected through a 5-point Likert scale questionnaire and analyzed using multiple linear regression with IBM SPSS. The results show that: (1) responsiveness has a positive and significant effect on purchase decisions (t = 5.517; p = 0.000) with the most dominant influence (β = 0.576); (2) sales promotion has a positive and significant effect on purchase decisions (t = 3.122; p = 0.003); and (3) both variables simultaneously have a significant effect (F = 122.798; p = 0.000) with a coefficient of determination (Adjusted R²) of 0.750, meaning 75.0% of the variation in purchase decisions can be explained by the model. These findings provide managerial implications that automotive dealers must prioritize improving the problem-solving competence of sales personnel and redesigning promotions oriented toward tangible benefits.